Options for a reliable cryogenic supply for the FAIR facility. (April 2019) - Kauschke, M; Kollmus, H; Eisel, T; Schroeder, CH; Streicher, B; Xiang, Y
Abstract: FAIR, which is currently being built at GSI, will provide particle beams with unprecedented intensity and quality. The facility's diversity makes it unique: ions of all natural elements of the periodic table as well as antiprotons can be accelerated. Hence the accelerators and the experimental infrastructure have to be extremely flexible in the adaptation to various operating schemes. The main accelerator, that will be realized within the starting phase of FAIR, is the SIS100 (SchwerIonenSychrotron 100 Tm). The superconducting magnets of SIS100 will to be hardly not to fast-ramped for several hours, which causes variations in the 4.5K heat load by factor 4. The larger cold mass and the higher liquid helium inventory is necessary for the Super-FRS (Superconducting FRagment Seperator), which will be supplied from the same cryo plant as SIS100.